2014
DOI: 10.5194/bgd-11-15991-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon export in the naturally iron-fertilized Kerguelen area of the Southern Ocean based on the <sup>234</sup>Th approach

Abstract: Abstract. The Kerguelen Plateau region in the Indian sector of the Southern Ocean supports annually a large-scale phytoplankton bloom which is naturally fertilized with iron. As part of the second KErguelen Ocean and Plateau compared Study expedition (KEOPS2) in austral spring (October–November 2011), we examined upper-ocean Particulate Organic Carbon (POC) export using the 234Th approach. We aimed at characterizing the spatial and the temporal variability of POC export production at high productivity sites ov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 54 publications
10
52
0
Order By: Relevance
“…During KEOPS 1, r ratios (MR / EP) remained low, ranging from 7 to 9 % of EP at A3, while during KEOPS 2, r ratios were slightly higher but decreased from 29 % (A3-1; first visit) to 13 %, 27 days later (A3-2; second visit). This variation in r ratio during KEOPS 2 is mostly due to an increase of EP (from 47 to 85 mg C m −2 day −1 ; Planchon et al, 2014) over the same period while MR showed little change. Although at this early stage of the season (spring) PP at A3-2 had already reached 2172 mg C m −2 day −1 , EP remained relatively low (85 mg C m −2 day −1 ).…”
Section: Station A3 On the Plateaumentioning
confidence: 97%
See 3 more Smart Citations
“…During KEOPS 1, r ratios (MR / EP) remained low, ranging from 7 to 9 % of EP at A3, while during KEOPS 2, r ratios were slightly higher but decreased from 29 % (A3-1; first visit) to 13 %, 27 days later (A3-2; second visit). This variation in r ratio during KEOPS 2 is mostly due to an increase of EP (from 47 to 85 mg C m −2 day −1 ; Planchon et al, 2014) over the same period while MR showed little change. Although at this early stage of the season (spring) PP at A3-2 had already reached 2172 mg C m −2 day −1 , EP remained relatively low (85 mg C m −2 day −1 ).…”
Section: Station A3 On the Plateaumentioning
confidence: 97%
“…up to the 0.01 % PAR level . EP data were estimated from 234 Th activities and 234 Th / POC ratios and are discussed in Planchon et al (2014). The thorium method integrates POC export over a 1-month period ( 234 Th half live is 24.1 days).…”
Section: Fate Of Exported Organic C In the Mesopelagic Zone And Deep mentioning
confidence: 99%
See 2 more Smart Citations
“…The extremely low carbon content of the sediment at station R-2, as evidenced by its near white colour, low diatom content (L. Armand, pers. obs., 2012) and low carbon export flux Planchon et al, 2014), suggests that MnO 2 enrichment in the surface sediments during redox cycling is more likely at R-2.…”
Section: Underlying Sediment Analysismentioning
confidence: 99%